New Transformation Rules for the EduBPMN Method to Generate Graphical User Interfaces from BPMN - Diaz, Eduardo (2022)
The EduBPMN method contains a set of transformation rules that allow the generation of Graphical User Interfaces (GUIs) from a BPMN model complemented by the UML class diagram. The article proposes new rules for the EduBPMN method based on BPMN primitives and operations of the UML classes. These rules can generate design alternatives for GUIs, each of which has been proposed to be represented by a stereotype. As a result of this work, four new rules and eight new stereotypes have been proposed to extend the EduBPMN method. For a better understanding of the contribution, it has been applied to an illustrative example of a project.